Urine Biochemistry of a Human Fetus with Urinary Tract Obstruction – A Case Report. (2nd January 2023) - Mongia, Alessandra; Milletti, Eva; Bonari, Alessandro; Lanzilao, Luisa; Pasquini, Lucia; Dani, Carlo; Fanelli, Alessandra
Abstract: Introduction: Fetal lower urinary tract obstruction (LUTO) can be mild or severe with oligohydramnios, renal dysplasia and pulmonary hypoplasia. Fetal urine biochemical markers correlate with fetal prognosis and, if favorable, surgical intervention is feasible. Methods: We report a patient in her 18th gestational week whose fetus was diagnosed with LUTO and underwent fetal urine sampling for calcium, sodium, chloride, beta2-microglobulin and total protein of the routine LUTO panel, with the addition of creatinine, glucose, phosphate, urea, ammonia, albumin, and NGAL. Results: Although the routine fetal urine biochemistry seemed to be favorably trending favorably, sodium, beta2-microglobulin, glucose, and urea did not decrease to the reference ranges, and ammonia and creatinine were lower than the reference ranges. Ultrasound demonstrated no improvement of the obstruction. Conclusions: This case highlights the need to acquire further experience with biochemical fetal urine markers in order to better manage LUTO.